Resilient modulus of freeze-thaw affected granular soils for pavement design and evaluation. - Cole, David M.; Cold Regions Research and Engineering Laboratory (U.S.); United States. Federal Aviation Administration. Program Engineering & Maintenance Service. (Washington, D.C. : Federal Aviation Administration, Program Engineering & Maintenance Service, 1986)
"July 1986." Cover title. Includes bibliographical references. Performed by the U.S. Army Cold Regions Research and Engineering Laboratory in cooperation with the Federal Highway Administration under contract no. Mode of access: Internet.